Endoscopic Inside-Out Mastoidectomy with the Ultrasonic Bone Aspirator. Issue 1 (January 2019) - Mehta, Rahul; Mankekar, Gauri; Mayland, Erica; Melder, Katie; Arriaga, Moises A.
We report our experience using the ultrasonic bone aspirator (UBA) for transcanal endoscopic "inside out" mastoidectomy. The UBA has irrigation, suction, and nonrotatory ultrasonic bone-removing technology in 1 handpiece, which makes it appropriate for bone removal during this procedure. The results of our study show that this technique is safe and effective for patients with cholesteatoma in a small sclerotic mastoid. We also discuss the nuances associated with using the UBA during endoscopic ear surgery.